Sonographic Appearance of Cricoid Cartilage Calcification in Healthy Children - Strauss, Simon (American journal of roentgenology (1976), 2000)
The purpose of this study was to determine the distribution pattern of calcification in cricoid cartilage of healthy children. Sonography of the neck was performed with a high-resolution linear array transducer to show the sides of the cricoid cartilage ring in both the sagittal and transverse planes. Twenty-three boys and 33 girls, who ranged in age from 6 to 17 years, were examined. Calcifications in the cartilage were characterized by number and size, distribution pattern, and side-to-side symmetry. Calcifications were seen either as small echogenic, nonshadowing foci or as larger irregular, echogenic areas with acoustic shadowing. Calcifications were found in 19 of the 23 boys and 26 of the 33 girls. The earliest cases were in three 7-year-old children. The incidence and number of echogenic foci generally increased with age. Most calcifications were in the center of the cartilage or distributed diffusely throughout. Side-to-side comparison of the number, size, and distribution pattern of the calcifications showed considerable variation. The sides of the cricoid cartilage ring could be seen on sonography in both the sagittal and transverse planes. Calcifications within the cartilage were readily shown and were found in children at an earlier age than previously reported.